Ludwig von Wolzogen and his Objections to Meditationes de prima philosophia - Gut, Przemysław (Ruch Filozoficzny, 2024)
The article presents one of the lesser known treatise produced within the Polish Socinian movement, written by Johann Ludwig von Wolzogen (ca. 1599-1661), under the title Breves in Meditationes Metaphysicas Renati Cartesii annotationes [Brief Notes on the Metaphysical Meditations of Rene Descartes]. It appeared in print in 1657 in Amsterdam and was ten years later reprinted in the series Bibliotheca Fratrum Polonorum. In its entirety, the text is intended as a polemic against Descartes’s views and written as a detailed commentary on the Meditationes de prima philosophia. Here I intend to demonstrate that Wolzogen’s treatise deserves a close scrutiny. First of all, it considerably contributes to our knowledge on the 17th century disputes around the Meditations on First Philosophy. Second, it represents the first substantive and fairly extensive discussion of Descartes’s philosophy to appear in the territory of the Polish-Lithuanian Commonwealth. Third, it is a treatise issued from the milieu of the Polish Socinians (the Polish Brethren) that has been recognized by recent research as having exerted a non-negligible influence upon the development of the progressive European thought of the period, both in the domain of theology and philosophy.